Long-term fat diet adaptation effects on performance, training capacity, and fat utilization - Helge, J. W. (Medicine & Science in Sports & Exercise, 2002)
It is well known that adaptation to a fat-rich carbohydrate-poor diet results in lower resting muscle glycogen content and a higher rate of fat oxidation during exercise when compared with a carbohydrate-rich diet. The net effect of such an adaptation could potentially be a sparing of muscle glycogen, and because muscle glycogen storage is coupled to endurance performance, it is possible that adaptation to a high-fat diet potentially could enhance endurance performance. Therefore, the first issue in this review is to critically evaluate the available evidence for a potential endurance performance enhancement after long-term fat-rich diet adaptation. Attainment of optimal performance is among other factors dependent also on the quality and quantity of the training performed. When exercise intensity is increased, there is an increased need for carbohydrates. On the other hand, consumption of a fat-rich diet decreases the storage of glycogen in both muscle and liver. Therefore, training intensity may be compromised in individuals while consuming a fat-rich diet. During submaximal exercise, fat for oxidation in muscle is recruited from plasma fatty acids, plasma triacylglycerol, and muscle triacylglycerol: the final question addressed in this review is which of these source(s) of fat contributes to the increased oxidation of fat during submaximal exercise after long-term fat diet adaptation.